ผลของสารสกัดจากขิงและข่าและอุณหภูมิการทำแห้งต่อสมบัติของฟิล์มโปรตีนถั่วเหลือง - บัณฑิตา จิตตประไพ (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
This study aimed to investigate the effect of concentration and oxidation state of aqueous ginger and galanga extracts, as well as drying temperature, on properties of soy protein film. To examine the effect of ginger or galangal extract on properties of the film, the extract was added at three different levels (2, 5 and 10% by weight of protein), in either oxidized or unoxidized state. Tensile strength of the films added with 5% ginger extract was higher than that of the control (p≤0.05). However, the film added with 10% ginger extract demonstrated a lower tensile strength than those with 5% addition. The films added with 2 or 5% galanga extract was found to show higher tensile strength than the control and the films added with the same amount of ginger extract. However, 10% galanga extract addition resulted in a significant decrease in tensile strength, as compared to that added with 5% galanga extract (p≤0.05). Regarding to oxidation state of the extracts, the oxidized extracts were shown to be more efficient in improving tensile strength than the unoxidized ones. The films added with extract were shown to possess greater, but with no statistically difference, elongation at break as compared to the control (p>0.05). Addition of ginger or galangal extract did not affect the film water vapor permeability, except for film added with 10% oxidized galanga extract which showed higher water vapor permeability than the control (p≤0.05). Film added with 10% oxidized galanga extract showed highest contact angle among all film samples. It was found that addition of ginger or galanga extract resulted in a decrease in transparency (as expressed in terms of %transmittance). Oxidation state posted a minimal effect on transparency of the film. In terms of color, hue angle of all film samples were found to be in the range of 80-90º, representing the yellow hue. Chroma was found to increase in extract-added samples. Total phenolic content, as determined by Folin-Ciocalteu assay, and antioxidant activity, as determined using 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay and ferric ion reducing antioxidant power (FRAP) assay, were found to be greater in extract-added films as compared to the control. To investigate the effect of drying temperature on the film properties, film added with either 5% oxidized ginger extract or 5% oxidized galanga extract was dried at 50, 60 and 70 ºC. It was found that the films dried at 70 ºC demonstrated the highest tensile strength, as compared to the films dried at other temperatures. However, elongation at break, water vapor permeability, water solubility and contact angle were minimally affected by drying temperature. Moreover, drying temperature did not affect transparency of the films added with ginger extract (p>0.05). In the case of films added with galanga extract, those dried at 60 or 70 ºC exhibited significantly lower transparency than those dried at lower temperatures (p≤0.05). Total phenolic content and antioxidant activity were found to increase in the films dried at lower temperature (50 ºC). However, those properties tended to decrease when the films were dried at 60 and 70 ºC.